Shelf life of papaya (carica papaya L.)as influenced by fruit maturity, holding time in ambient and 1-methylyclopropene - Jamiri, Sitti Rahma J. (2006)
The postharvest of two fruit maturities of Carica papaya cv. Kapoho to various holding times (0, 1, 2 days0 in ambient prior to treatment with 100 nl 1-1 1-5-15% yellow fruit (5-15Y) regardless of holding time. At 6 days after treatment (DAT), peel yellowing was slower in 5-15Y held for 2 days. At 9 DAT, visual quality was better in mature green fruit. Fruit were firmer while disease tended to be less severe in the treated 5-15Y lot. Weight loss was lower when held for 2 days. Shelf life and days to edible ripe stage (DERS) were longer in fruit held for 1 or 2 days. Days to disease occurrence (DDO) was delayed in mature green fruit held for 1 or 2 days and in 5-15Y held for 2 days. Relative to the control, fruit that were 5-15Y and held for 2 days prior to 1 MCP gave a 59% improvement in shelf life, 73% delay in DERS and 51% delay in DDO. Responses of 5-15Y fruit held for a day prior to treatment with various 1-MCP concentrations (0.50, 100, 150 nl l-1) were also determined. 1-MCP at 100 nl l-1 resulted in a longer shelf life of 14.3 days or 30% improvement in shelf life, less yellow but firmer fruit at 9 DAT as well as delays in DERS and DDO at 23 and 25%, respectively. Respiration rate was lower in treated 5-15Y regardless for holding time. All treated fruit for a day or two in ambient conditions prior to treatment with 100 nl l-1 1-MCP is effective in prolonging shelf life of Kapoho papaya